Lamivudine’s efficacy and safety in preventing mother-to-child transmission of hepatitis B: A meta-analysis - Pooyan Khalighinejad; Seyed Moayed Alavian; Mohammad Gholami Fesharaki; Rozita Jalilianhasanpour (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Mother-to-child transmission (MTCT) is a common transmission mode of hepatitis B virus (HBV). It has been shown that the infection may occur in some infants despite the use of immunoprophylaxis, and many studies have demonstrated the efficacy of antivirals such as lamivudine to reduce such events. Materials and Methods: A meta-analysis was conducted concerning the efficacy and safety of lamivudine during pregnancy, in the prevention of vertical transmission of HBV infection. Studies were identified by searching various databases up to January 2016 for variations of the following phrase: “lamivudine AND (pregnancy or pregnant) AND (HBV or hepatitis).” Subjects who had received lamivudine were included in the case group, and those who had not were included in the control group. Results: Our search identified a total number of 881 citations, of which 25 studies (with a total number of 2,667 pregnant women) were included in the meta-analysis. The analysis showed a significant difference between the seropositive HBsAg infants from the case and control groups (RR= 16.97, 95% confidence interval 8.36-34.45), which is the most critical factor in determining the MTCT of HBV. No significant difference was reported between the prevalence of side effects in the case and control groups. Conclusion: This meta-analysis strongly suggests the use of lamivudine in the prevention of HBV vertical transmission in carrier pregnant women with the HBV DNA levels greater than 106 copies/mL. And for women with the HBV viral loads lower than 106 copies/mL, we suggest clinicians to examine the use of lamivudine on a case-to-case basis, noting that lamivudine seems to be a safe drug for the mother and the fetus. Cite this article as: Khalighinejad P, Alavian SM, Gholami Fesharaki M, Jalilianhasanpour R. Lamivudine’s efficacy and safety in preventing mother-to-child transmission of hepatitis B: A meta-analysis. Turk J Gastroenterol 2019; 30: 66-74.